Modelisation numerique des couplages en thermomecanique des solides - Chrysochoos, Andre; Peyroux, Robert (European Journal of Computational Mechanics, 1997)
In a first part the thermodynamic framework used to introduced the behavioral constitutive equations of solid materials is reminded. Using illustrative examples, the different terms of the energy balance are introduced, specially those due to thennomechanical coupling mechanisms. In a second part the main concepts on multiscale approach are introduced, focussing on coupling aspects, and the way of embedding coupled constitutive equations in a finite element code is discussed. We finally present four applications to illustrate the abovementioned approaches.